Depth distribution of the amoebic gill disease agent, Neoparamoeba perurans, in salmon sea-cages - Wright, DW; Barbara Nowak; Oppedal, F; Andrew Bridle; Dempster, T (2015)
Identifying where and when parasites occur in farming environments is vital to understand transmission dynamics and develop preventative measures that reduce host-parasite encounters. A major parasite concern for Atlantic salmon farming is Neoparamoeba perurans , a marine amoeba causing the potentially fatal Amoebic Gill Disease (AGD), for which few control options exist. We explored whether free-living N. perurans abundance differs among depths in commercial Atlantic salmon sea-cages. Water samples from the surface to 10 m depth at multiple cage sites and times, collected by a Niskin bottle and subjected to qPCR analysis, revealed N. perurans abundance was influenced by depth at the time of year when amoeba numbers were highest, with more amoebae in surface waters. No distinct depth patterns were observed when amoebae were in low abundance. Across all times, temperature and salinity were largely homogenous throughout cage depths. Possible factors explaining the presence of amoebae at the surface are discussed. Our results suggest excluding caged salmon from upper cage depths where N. perurans is more abundant could be an effective management strategy to reduce the speed at which initial infections occur and delay the development of AGD outbreaks.